Proaktivnost slepih in slabovidnih pri dojemanju abstraktne in figuralne umetnosti - Herzog, Jerneja (Revija za elementarno izobraževanje, 2014)
In the paper we present the theoretical starting points about comprehending the language of art in the blind and partially sighted. The central part of the article is dedicated to the presentation of the outcomes of a case study, in which different methods of working with the blind and partially sighted in comprehending abstract and figurative art through their own activity were tested. As blind and partially sighted persons have increasingly been involved in usual life and blind and partially sighted children also get included in the education systems both in schools and in museums, we have found it important to be aware of the importance of selecting appropriate methods of bringing the world of art closer to this group.
Keywords: fine arts; osebe s posebnimi potrebami; slepi; blindness; slabovidni; methods of work; museum pedagogy; likovna umetnost; visual arts; muzeji; muzejska pedagogika